Exploring engineering student perspectives: utilizing commercial mobile apps for environmental ergonomics assessment in community-based projects - Nadhrah Haziqah Ramli,; Mohd Faizal Mat Tahir,; Mohd Anas Mohd Sabri,; Meor Iqram Meor Ahmad,; Nor Kamaliana Khamis, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Through a community-based project, this study seeks to investigate students' perceptions of the use of commercial mobile applications in the assessment of environmental ergonomics. This study aims to combine mobile technology with community needs in a comprehensive endeavour to increase knowledge of how the physical environment affects human well-being. Community refers to the general public in homes, in car workshops, and in university laboratories. This study employs a mixed-method approach consisting of interviews and questionnaires to determine the perspectives of students regarding this endeavour. The results of the study indicate that through participation in community-based initiatives, their understanding of crucial aspects of environmental ergonomics increased significantly. Students are enthusiastic about using mobile applications to conduct ergonomics evaluations. This study will increase students' awareness of the significance of joint ergonomics and encourage the community to implement comparable initiatives to enhance the well-being of the whole. This study concludes that the use of commercial mobile applications in the evaluation of ergonomics can have a positive effect on student comprehension and community awareness of the significance of the human-physical environment relationship. Therefore, efforts to integrate mobile technology into the community-centered project methodology should continue to strengthen this relationship over time.